2021
DOI: 10.1002/ejsp.2759
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of racism: A new construct that predicts failure to recognize and confront racism

Abstract: Often people who may not personally express racist beliefs nevertheless have a passive orientation to racism and tolerate racist statements and acts by others. We examine individual differences in willingness to accept racist views or acts in others, labelled tolerance of racism (TOR), in four online survey studies (total N = 2,008). We demonstrate that TOR is distinct from, although correlated with, established forms of bias, such as symbolic and modern racism and social dominance orientation, which measure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Lastly, person-centered analyses are sensitive to the kind of variables used (Osborne & Sibley, 2017). Future studies should test if the subgroups we identified are specific to attitudes on the Sinterklaas festivities and the Black Pete figure or generalizable to broader topics such as nationalism (a belief in the superiority of one's nation; Kosterman & Feshbach, 1989), fear of change of cultural traditions, and tolerance of racism (Hunt et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lastly, person-centered analyses are sensitive to the kind of variables used (Osborne & Sibley, 2017). Future studies should test if the subgroups we identified are specific to attitudes on the Sinterklaas festivities and the Black Pete figure or generalizable to broader topics such as nationalism (a belief in the superiority of one's nation; Kosterman & Feshbach, 1989), fear of change of cultural traditions, and tolerance of racism (Hunt et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Research provides support for this assumption in various ways. For instance, SDO is associated with resistance to having an intercultural dialogue with an ethnic outgroup member regarding racism (Cargile, 2017), unwillingness to apologize to ethnic outgroup members for harm suffered during colonial times (Mifune et al, 2019), a lower tendency to classify a potentially prejudiced situation as being racist (Miller & Saucier, 2018), tolerance of racism (Hunt et al, 2021), and a greater likelihood of framing social progress made by marginalized ethnic groups as a 'loss' for the dominant ethnic group (Eibach & Keegan, 2006). Additionally, although national identification and SDO are associated with one another, SDO is consistently linked with negative attitudes towards marginalized groups cross-culturally, while national identification is not (Anderson & Ferguson, 2018;Pratto et al, 2013;Thomsen et al, 2008).…”
Section: Identity and Sdomentioning
confidence: 99%
“…Pro-Alt-Right reactions tapped into tolerance of their activities and ideas, but not necessarily explicit support for, or willingness to join, the movement. To use the words of Horton (1996, p. 26) in how tolerance is described, we conceptualized pro-Alt-Right attitudes as being about the “deliberate decision to refrain from prohibiting, hindering, or otherwise coercively interfering with conduct of which one disapproves.” Our conceptualization therefore mirrors recent work on tolerance of racism, which captures the phenomenon whereby people may not personally express racist beliefs but are nonetheless lenient when it comes to racism: they are likely to go along with racist acts and show less concern about the consequences of racism (Hunt et al, 2021). One way to show tolerance and leniency towards the Alt-Right is by believing that their speech qualifies as free speech, no matter how inflammatory it may seem (Uyehara, 2018).…”
Section: Public Reactions To the Alt-rightmentioning
confidence: 92%
“…Finally, we measured political orientation as a less explicit proxy for the likelihood of harboring racial prejudice—reasoning that perhaps reporting one’s political orientation would be less vulnerable to the very social desirability concerns that we were investigating. Republicans are significantly less likely to believe that racism is still a problem and that the country needs to continue to make changes for racial equality (Neal, 2017; Pew Research Center, 2017) and are less supportive of the Black Lives Matter movement than are Democrats (Hunt et al, 2021; Neal, 2017) and independents (Hunt et al, 2021). Republicans are more likely to say that Black people are responsible for the economic and social disadvantages they face, whereas Democrats are more likely to say that these disadvantages are the result of racial discrimination (Pew Research Center, 2017).…”
Section: Potential Moderators: Individual Differences In Prejudice-re...mentioning
confidence: 99%